Health and Hand Hygiene Education at Ar-Rhida Kindergarten Through Interactive Activities: Edukasi Kesehatan dan Kebersihan Tangan di TK Ar-Rhida Melalui Aktivitas Interaktif - Indrayani Dalimunthe, Gabena; Rani, Zulmai; Yuniarti, Rafita; Sari Lubis, Winda; Sartika Daulay, Anny (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Hand health and hygiene are important aspects in preventing disease transmission, especially in early childhood who are at high risk of infection due to poor hygiene habits. This Community Service (PKM) activity was carried out with the aim of improving the understanding and ability of early childhood children in maintaining hand hygiene through an interactive educational approach at Ar-Rhida Kindergarten. The method used included a game-based educational approach with 30 children aged 4 to 5 years old involved in this activity, which consisted of handwashing education sessions using songs, storybooks/picture posters, and direct practice simulations. Data collection techniques used included pre-tests and post-tests, as well as direct observation of children's behavior during the activity. The measurement tools for the success of the activity included a visual-based knowledge assessment sheet (pictures) and a checklist for observing handwashing behavior according to procedures. Based on the results of the activity, there was a significant increase of around 85% in the aspect of knowledge and skills in washing hands correctly after the implementation of the education, increasing by up to 90%. The conclusion of this activity is that interactive methods are effective in increasing awareness and skills of early childhood regarding hand health and hygiene. This program is recommended to be implemented sustainably by involving the active role of teachers and parents in supporting the formation of clean living habits from an early age.